1987
DOI: 10.1111/j.1399-6576.1987.tb02671.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal therapy: rationale, technique, clinical results

Abstract: In 35 patients a subcutaneously implanted injection port/reservoir was used to provide intrathecal morphine to relieve pain due to cancer. The reservoir offers an alternative to rather expensive devices. It can be used for repeated injections or for infusion. It is easy to locate and facilitates ambulatory treatment. The injections were carried out by members of the patient's family after they had been taught how to do it. Initially, doses of 0.25–0.5 mg of morphine resulted in pain relief for 14 to 24 hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Fortunately it is often only transient. 48,84 Cheng and colleagues 24 reported an incidence of 36% during the first week and 0% after week 2 of intrathecal morphine therapy. • In general, pruritus is uncommon in chronic administration of morphine.…”
Section: Pruritismentioning
confidence: 99%
“…Fortunately it is often only transient. 48,84 Cheng and colleagues 24 reported an incidence of 36% during the first week and 0% after week 2 of intrathecal morphine therapy. • In general, pruritus is uncommon in chronic administration of morphine.…”
Section: Pruritismentioning
confidence: 99%
“…Repeated morphine administration induces tolerance in animals and humans regardless of the administration route (Cichewicz and Welch, 2003;Younger et al, 2008). Tolerance to morphine analgesia develops at peripheral, spinal, and supraspinal sites (Leavens et al, 1982;Madrid et al, 1987;Kolesnikov et al, 1996;Ness and Follett, 1998;Kest and Hopkins, 2001;Bao et al, 2015) through complex mechanisms that are not fully understood. Numerous studies have indicated that the activation of pronociceptive chemicals contributes to morphine tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pure, freeze-dried diamorphine is widely and easily available in UK medical practice. Most of the evidence for the use of intrathecal opioids in cancer pain refers to morphine 7,20,[36][37][38][39][40][41][42][43][44][45][46][47] To date there is little published evidence on the use of intrathecal diamorphine in this population, although it is used widely in anaesthetics and chronic pain in the UK. The pharmacokinetics of morphine and diamorphine in the intrathecal space are different.…”
Section: Drugsmentioning
confidence: 99%